Central nervous pathways of insulin action in the control of metabolism and food intake. Issue 6 (June 2020) - Kullmann, Stephanie; Kleinridders, André; Small, Dana M; Fritsche, Andreas; Häring, Hans-Ulrich; Preissl, Hubert; Heni, Martin
Summary: Insulin acts on the CNS to modulate behaviour and systemic metabolism. Disturbances in brain insulin action represent a possible link between metabolic and cognitive health. Current findings from human research suggest that boosting central insulin action in the brain modulates peripheral metabolism, enhancing whole-body insulin sensitivity and suppressing endogenous glucose production. Moreover, central insulin action curbs food intake by reducing the salience of highly palatable food cues and increasing cognitive control. Animal models show that the mesocorticolimbic circuitry is finely tuned in response to insulin, driven mainly by the dopamine system. These mechanisms are impaired in people with obesity, which might increase their risk of developing type 2 diabetes and associated diseases. Overall, current findings highlight the role of insulin action in the brain and its consequences on peripheral metabolism and cognition. Hence, improving central insulin action could represent a therapeutic option for people at an increased risk of developing metabolic and cognitive diseases.